Hemodialisis Sustained Low-Efficiency Dialysis: Indikasi dan Penerapannya - Yenny Kandarini; I Made Arya Winangun (DiscoverSys Inc., 2021)
Acute kidney injury (AKI) and chronic kidney disease (CKD) are still a global health burden. The global incidence of AKI reaches 21.6% with a mortality rate of 23.9%. AKI is associated with the need for renal support therapy of 4-5% patients. AKI that persists in a long period can lead to CKD. CKD are associated with increased economic burdens, risk of cardiovascular disease and death. One of treatments to prevent morbidity and death in AKI and CKD is through hemodialysis. Sustained low-efficiency dialysis (SLED) resembles the form of conventional intermittent hemodialysis (IHD) but by slowing down the blood flow and the dialysis flow with the duration being extended to 6-12 hours can reduced the risk of hemodynamic instability compared to IHD. A recent meta-analysis and systematic review stated that there were no differences between SLED and continous renal replacement therapy (CRRT) regarding the recovery of renal function in AKI, days required for recovery and the incidence of hypotension in patients in ICU. SLED provides results that are almost the same as 24 hours continuous hemodialysis of CRRT in patients with unstable hemodynamics but with more affordable cost. Understanding the use and mechanism of SLED is important to manage patients with AKI and CKD in unstable hemodynamic conditions. Acute kidney injury (AKI) dan penyakit ginjal kronik (PGK) masih menjadi beban kesehatan di dunia. Angka insiden global AKI mencapai 21,6% dengan angka mortalitas 23,9%. AKI diasosiasikan dengan perlunya terapi pendukung ginjal pada 4-5% pasien. AKI yang menetap dalam periode yang lama dapat mengarah ke PGK. PGK diasosiasikan dengan meningkatnya beban ekonomi, risiko penyakit kardiovaskular dan kematian. Salah satu penanganan untuk mencegah morbiditas dan kematian pada AKI dan PGK yaitu melalui hemodialisis. Sustained low-efficiency dialysis (SLED) menyerupai bentuk hemodialisis konvensional intermittent hemodialysis (IHD) namun dengan memperlambat aliran darah dan aliran dialisis dengan durasi yang diperpanjang menjadi 6-12 jam dapat mengurangi risiko instabilitas hemodinamik dibandingkan IHD. Sebuah meta analisis dan review sistematik menyebutkan tidak ada perbedaan antara SLED dan continous renal replacement therapy (CRRT) pada pemulihan fungsi ginjal pada AKI, hari yang diperlukan untuk pemulihan dan kejadian hipotensi pada pasien di ICU. SLED menunjukkan hasil yang hampir sama seperti pada hemodialisis yang dilakukan berkelanjutan selama 24 jam pada CRRT pada pasien hemodinamik yang tidak stabil namun dengan biaya yang lebih terjangkau. Pemahaman mengenai penerapan dan mekanisme SLED menjadi penting untuk menangani pasien AKI dan PGK dengan kondisi hemodinamik yang tidak stabil.